2019
DOI: 10.1177/0269216319853488
|View full text |Cite
|
Sign up to set email alerts
|

Accurate prognostic awareness and preference states influence the concordance between terminally ill cancer patients’ states of preferred and received life-sustaining treatments in the last 6 months of life

Abstract: Background: Factors facilitating/hindering concordance between preferred and received life-sustaining treatments may be distorted if preferences and predictors are measured long before death. Aim: To examine factors facilitating/hindering concordance between cancer patients’ preferred and received life-sustaining-treatment states in their last 6 months. Design: Longitudinal, observational design. Setting/participants: States of preferred and received life-sustaining treatments (cardio-pulmonary resuscitation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
(74 reference statements)
1
25
0
Order By: Relevance
“…On the other hand, this review also found associations of accurate PA with positive aspects such as better communication with family and health care providers, 14 feeling of having control 32 and inner peace 35 . Recent longitudinal studies showed that prognostic discussion can help in building therapeutic alliance 78 and patients with accurate prognostic awareness are more likely get the treatment which they prefer 67 . One potential solution for this dilemma of potential negative aspects of prognostic disclosure might be in tailoring communication about prognosis according to patients' preferences rather than focus on achieving accurate prognostic awareness itself while hoping that this will ease patients' suffering.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand, this review also found associations of accurate PA with positive aspects such as better communication with family and health care providers, 14 feeling of having control 32 and inner peace 35 . Recent longitudinal studies showed that prognostic discussion can help in building therapeutic alliance 78 and patients with accurate prognostic awareness are more likely get the treatment which they prefer 67 . One potential solution for this dilemma of potential negative aspects of prognostic disclosure might be in tailoring communication about prognosis according to patients' preferences rather than focus on achieving accurate prognostic awareness itself while hoping that this will ease patients' suffering.…”
Section: Discussionmentioning
confidence: 73%
“…Accurate PA was also associated with less utilization of intravenous chemotherapy, 17,62 intubation, and mechanical ventilation 59 . Patients with accurate prognostic awareness received often preferred type of care 67 . On the other hand, patients with accurate PA tend to have shorter survival than patients with inaccurate PA 17, 23, 24, 26, 39, 44 .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the available evidence shows that most patients prefer to be informed about their diagnosis and prognosis, even if it is poor, and their preferences for health information are not related to their level of prognostic awareness 10–12 . Several studies also showed that accurate prognostic awareness can positively influence achieving goal‐concordant care at the end of life 13–15 . Although we could expect some specific factors being associated with prognostic awareness of patients in the Eastern Europe, recent systematic reviews did not find any research published on prognostic awareness from this region 6,7,9 …”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients who recognized that they were terminally ill preferred symptom-directed EOL care over life-extending therapy [ 6 , 42 ]. Due to the low prevalence of cancer patients’ prognostic disclosure, it is critical to promote rational communication between physicians and patients regarding accurate disclosure of prognosis to help patient make appropriate LST preferences [ 43 ].…”
Section: Discussionmentioning
confidence: 99%